A triangle: Spatial processes of urbanization and political power in 19th-century Tabora, Tanzania - Karin Pallaver (Afriques)
This article aims to contribute to the study of the urbanization of caravan-related towns in 19th-century Tanzania by unpacking the way multiple settlements merged into a town that came to be known as Tabora. By following the development of the three settlements that formed Tabora—Kwikuru, Kwihara and Sokoni—this article shows how the urban structure of Tabora was shaped by its commercial role, by the presence of a political power that influenced the organization of the urban space to affirm its authority and display its wealth, and by a community of coastal traders with their own political representative, the wali. The analysis points towards the profound relationship between spatial processes of urbanization and the exercise of political power.